2004
DOI: 10.1158/1055-9965.epi-03-0150
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Adducts of Naphthalene Metabolites as Biomarkers of Exposure to Polycyclic Aromatic Hydrocarbons

Abstract: We investigated the utility of adducts formed by the reaction of the naphthalene metabolites naphthalene-1,2-oxide, 1,2-naphthoquinone (1,2-NPQ), and 1,4-naphthoquinone (1,4-NPQ) with serum albumin (Alb) as biomarkers of exposure to polycyclic aromatic hydrocarbons. Cysteinyl serum Alb adducts of 1,2-and 1,4-NPQ (1,2-NPQ-Alb and 1,4-NPQ-Alb, respectively) but not of naphthalene-1,2-oxide were detected in 28 coke oven workers and 22 controls from the steel industry of northern China. The median level of 1,2-NPQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 37 publications
2
14
0
2
Order By: Relevance
“…This finding is consistent with a 3% reduction in naphthoquinone-albumin adduct level, and 2% reduction in 1,4-benzoquinone-albumin adduct level per year of increase in workers exposed to PAHs (Rappaport et al 2002; Waidyanatha et al 2004b). Experimental evidence also suggests that percutaneous absorption of some chemicals decrease with increasing age (Christophers & Kligman 1965; Tagami 1972; Roskos et al 1989).…”
Section: Discussionsupporting
confidence: 69%
“…This finding is consistent with a 3% reduction in naphthoquinone-albumin adduct level, and 2% reduction in 1,4-benzoquinone-albumin adduct level per year of increase in workers exposed to PAHs (Rappaport et al 2002; Waidyanatha et al 2004b). Experimental evidence also suggests that percutaneous absorption of some chemicals decrease with increasing age (Christophers & Kligman 1965; Tagami 1972; Roskos et al 1989).…”
Section: Discussionsupporting
confidence: 69%
“…Hemoglobin and albumin adducts of 1,2-naphthoquinone and 1,4-naphthoquinone were also detected after administration of naphthalene to F344 rats (Waidyanatha et al, 2002(Waidyanatha et al, , 2004.…”
Section: Mass Spectrometry and Protein Adductsmentioning
confidence: 90%
“…This technique has been applied to the measurement of benzene oxide adducts to hemoglobin (Yeowell-O'Connell, McDonald, & Rappaport, 1996), of 1,2 and 1,4-benzoquinone adducts (Waidyanatha, Yeowell-O'Connel, & Rappaport, 1998) and of naphthalene oxide (Waidyanatha et al, 2002(Waidyanatha et al, , 2004.…”
Section: Mass Spectrometry and Protein Adductsmentioning
confidence: 99%
“…8B). Differences of this magnitude are consistent with results from the few studies that reported concentrations of targeted HSA-Cys 34 adducts in smokers and nonsmokers, namely, those of benzene oxide (0.113 pmol/mg HSA in nonsmokers versus 0.094 pmol/mg HSA in smokers) (35), 1,4-benzoquinone (0.687 pmol/mg HSA in nonsmokers versus 0.760 pmol/mg HSA in smokers) (36), styrene-7,8-oxide (2.54 pmol/mg HSA in nonsmokers versus 3.49 pmol/mg HSA in smokers) (37), 1,4-naphthoquinone (0.045 pmol/mg HSA in nonsmokers versus 0.061 pmol/mg HSA in smokers) (38), 1,2-naphthoquinone (0.056 pmol/mg HSA in nonsmokers versus 0.062 pmol/mg HSA in smokers (38), and the N-nitroso metabolite of 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) (0.005 pmol/mg HSA in nonsmokers versus 0.005 pmol/mg HSA in smokers) (39).…”
Section: Fs-srm Of T3 Adducts From Human Samples-followingmentioning
confidence: 99%